Social Interaction Services as Mediation between Corporate Image and Social Interaction Satisfaction - Kurniawan, Arief Adhy; Kartawan, Kartawan; Setyawati, Srimurni; Nida, Faridatun (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
MSMEs are currently growing rapidly, especially MSMEs that provide social interaction services in restaurants or cafes. Social interaction develops along with the existence of social media. This has resulted in competition for MSMEs as social interaction service providers. Consumers who interact socially will return to transactions if they feel satisfaction when interacting socially. Therefore, realizing customer satisfaction is important for MSMEs, so that consumers want to come back and recommend it to others. This research aims to examine the effect of corporate image on social interaction satisfaction, examine the effect of social interaction services on social interaction satisfaction and examine the role of social interaction in mediating corporate image with social interaction satisfaction. This research was conducted on consumers who are socially interacting in restaurants or cafes in Purwokerto. The study was conducted in 58 restaurants or cafes with a consumer sample size of 310 respondents. The analytical tool used is a structural equation model (SEM) with PLS software. This study concludes with the effect of corporate image on social interaction satisfaction. There is an influence of social interaction on the satisfaction of social interaction and social interaction services can mediate the company's image with the satisfaction of social interaction.